Fabrication and superhydrophobic behavior of fluorinated microspheres - Muoz-Bonilla, A (Langmuir : the ACS journal of surfaces and colloids, 2010)
We describe the preparation of fluorinated microspheres by precipitation polymerization and their use to fabricate superhydrophobic surfaces. For that purpose, two different approaches have been employed. In the first approach, a fluorinated monomer (either 4-fluorostyrene or 2,3,4,5,6-pentafluorostyrene) was added to the initial mixture of monomers constituted by styrene (S) and divinylbenzene (DVB). The second approach is based on the encapsulation of a block copolymer, polystyrene-b-poly(2,3,4,5,6-pentafluorostyrene), during the polymerization of the monomers (S and DVB), thus enabling the formation of particles with perfluorinated chains instead of single functional groups at the interface. Both approaches led to narrow polydisperse particles with fluoro-functional groups at the interface as demonstrated by scanning electron microscopy (SEM), infrared (IR) spectroscopy, and X-ray photoelectron spectroscopy (XPS). Surface array of particles obtained by simple solvent casting presented superhydrophobic behavior with contact angles of water droplets of ca. 160-165°